PENGARUH PROFITABILITAS, LAVERAGE TERHADAP AGRESIVITAS PAJAK PADA SUB SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA PERIODE 2017-2019 - Anggi Helena Br Tarigan; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This study aims to see the effeck of profitability on tax aggressivenees. Profitability is measured using the return on assets (ROA) formula and leverage is measured by the equity ratio and aggressiveness is measured by (ETR) effective tax rate. The method used in this research is quantitative method. And this research was conducted on manufacturing companies listed on the Indonesia stock exchange in the 2017-2019 period. As a population by using purpose sampling technique and 20 companies were selected as samples. This stdy uses primary data through financial reports. In this study, the independent variable is profitability (X1) and leverage (X2), while the dependent variable is tax aggressiveness (Y). From the results of multiple linear analysis, profitability and leverage have significant effect on tax aggressiveness, where profitability is 0,611 > 0,05 with count -512 and leverage 0.581>0.05 with count -555. The profitability and leverage have negative effect on tax aggressiveness.